Elevated sCD40L in Secondary Progressive Multiple Sclerosis in Comparison to Non-progressive Benign and Relapsing Remitting Multiple Sclerosis. (19th October 2021) - Wu, Qi; Wang, Qin; Yang, Jennifer; Martens, Jacob WS; Mills, Elizabeth A; Saad, Aiya; Chilukuri, Pavani; Dowling, Catherine A; Mao-Draayer, Yang
Background: The long-term prognosis of relapsing-remitting multiple sclerosis (RRMS) is usually unfavorable as most patients transition to secondary progressive multiple sclerosis (SPMS) with accumulative disability. A rare form of non-progressive multiple sclerosis (MS) also exists, known as benign MS (BMS or NPMS), which lacks disease progression defined as Expanded Disability Status Scale (EDSS) ≤3 after 15 years of disease onset without treatment. Purpose: Our study aims to identify soluble plasma factors predicting disease progression in multiple sclerosis (MS). Research Design and Study Sample: We utilized Luminex multiplex to analyze plasma levels of 33 soluble factors, comparing 32 SPMS patients to age-, sex-, and disease duration-matched non-progressive BMS patients, as well as to RRMS patients and healthy controls. Results: Plasma levels of EGF, sCD40L, MCP1/CCL2, fractalkine/CX3CL1, IL-13, Eotaxin, TNFβ/LTα, and IL-12p40 were significantly different between the various types of MS. Plasma sCD40L was significantly elevated in SPMS compared to BMS and RRMS. The combination of MCP1/CCL2 and sCD40L discriminated between RRMS and SPMS. MCP1/CCL2 was found to be the most effective classifier between BMS and RRMS, while BMS was most effectively distinguished from SPMS by the combination of sCD40L and IFNγ levels. Conclusions: These differences may facilitate personalized precision medicine and aid in the discovery of new therapeutic targets for disease progression through the improvement of patient stratification.